A utilização de recursos audiovisuais nas aulas de ciências: um estudo com professores polivalentes. - Pontes, Josenilda Ferreira Vieira de. (2013)
This work completion course consists of a research that aims to present an analysis of data and generate discussion about the use of audiovisual resources in science classes. For our research we focus on classes taught by teachers of the early years of elementary school. Methodology applied in semi-open questionnaires to a group of teachers multipurpose municipal schools in a city in the state of Paraíba, in order to check if they use and how to use visual aids to teach the course content of Natural Sciences. After collecting and analyzing the data concluded that teachers make use of audiovisual resources exist in schools, but not with the potential that the resource can offer, or as often as necessary to stimulate children to learn in a playful manner and illustrative content of discipline of Natural Sciences.